Resolving the prevalence of somatic transposition in Drosophila - Treiber, C; Waddell, S (eLife Sciences Publications, 2017)
Somatic transposition in mammals and insects could increase cellular diversity and neural mobilization has been implicated in age-dependent decline. To understand the impact of transposition in somatic cells it is essential to reliably measure the frequency and map locations of new insertions. Here we identified thousands of putative somatic transposon insertions in neurons from individual Drosophila melanogaster using whole-genome sequencing. However, the number of de novo insertions did not correlate with transposon expression or fly age. Analysing our data with exons as "immobile genetic elements" revealed a similar frequency of unexpected exon translocations. A new sequencing strategy that recovers transposon : chromosome junction information revealed most putative de novo transposon and exon insertions likely result from unavoidable chimeric artefacts. Reanalysis of other published data suggests similar artefacts are often mistaken for genuine somatic transposition. We conclude that somatic transposition is less prevalent in Drosophila than previously envisaged.